Patent Productivity of German Professors over the Life Cycle - Sidonia von Ledebur (Philipps-University Marburg, Department of Geography, 2009)
The paper studies the patent productivity of scientists over their life cycle. The incentives for patenting and for publishing are compared and how they shape life cycle productivity. In most empirical studies, publication productivity decreases at the end of the scientific career. In contrast, the analytical model given here suggests an increase of patent productivity over the life time. In the empirical part the patents of nearly 1000 German patent active professors are analyzed. The empirical findings support the theoretical prediction that patent productivity does not decline for older scientists.
Keywords: O33; O34; J24; 330; university patenting; patent productivity; scientific productivity; age and productivity; Germany